Conocimiento y actitudes de los docentes de primaria frente a las dificultades escolares de alumnos de las instituciones educativas Públicas de Huánuco, 2013 - Cisneros Martinez, Leo (2017)
This research aimed to identify the level of knowledge and attitudes of the primary teachers facing school difficulties of students in public educational institutions of Huánuco; pointed out this comparative differences between the institutions are established in the designated variables. For its realization was selected nine educational institutions of Huánuco, then taking a representative sample of 128 teachers equitably distributed according to the number of teachers working in the educational institution. Used two questionnaires, one of 20 items measuring the level of knowledge and another with 60 items that vlora the orientation of attitudes. . The results show in a general way that teachers have a low level of knowledge about school difficulties, but emphasizes the positive and favorable attitudes presented against them; This last result allows us to predict the provision that teachers have to act positively in schools when these difficulties arise. Finally, from the comparative point of view there are significant differences between educational institutions in reference to the level of knowledge and attitudes towards the difficulties of learning.